Assessment of global left ventricular excursion using three‐dimensional dobutamine stress echocardiography to identify significant coronary artery disease. Issue 10 (16th June 2016) - Hoogslag, Georgette E.; Joyce, Emer; Bax, Jeroen J.; Ajmone Marsan, Nina; Delgado, Victoria
Abstract : Background: Quantitative three‐dimensional (3D) dobutamine stress echocardiography (DSE) for myocardial ischemia detection may be an adjuvant to left ventricular (LV) wall‐motion analysis. The aim of the current study was to assess the association between global 3D LV excursion during DSE and the presence of significant coronary artery disease (CAD) on coronary angiography. Methods: Three‐dimensional DSE was performed in 40 patients (67±12 years, 68% male) who underwent subsequent coronary angiography (median 1.6 months later). Using 3D echocardiography, global LV excursion was measured (in a total of 680 segments) at rest and peak dose and the change between stages was calculated (peak‐rest=∆global LV excursion). Significant CAD was defined as >70% stenosis on coronary angiography. Results: In total, 25 patients (63%) demonstrated significant CAD on coronary angiography. At rest, global LV excursion was similar in patients with and without significant CAD (5.1±0.2 vs 5.0±0.2 mm, P =.74). However, patients with significant CAD demonstrated a worsening in global LV excursion from rest to peak stress (from 5.1±0.2 to 4.1±0.2 mm, P <.001), while global LV excursion in patients without significant CAD remained unchanged (from 5.0±0.2 to 5.5±0.2 mm, P =.10). After adjusting for clinically relevant characteristics, ∆global LV excursion was independently associated with significant CAD (odds ratio 0.29, 95% confidence interval 0.12–0.72, P =.008). Conclusions: Analysis of 3D echocardiographic LV excursion at global level on full‐protocol DSE may be a helpful tool to detect CAD on coronary angiography.